In vitro evaluation of fungicides, botanicals and biocontrol agents against Macrophomina phaseolina (Tassi.) Goid. - The causal organism of root rot of sesame: IN VITRO EVALUATION OF FUNGICIDES, BOTANICALS AND BIOAGENTS AGAINST M. PHASEOLINA - C S KARIBASAPPA; BHARATI N BHAT; S CHANDER RAO (Journal of Oilseeds Research, 2018)
The efficacy of six fungicides was evaluated in vitro by poisoned food technique which revealed that all the fungicides were effective in inhibiting mycelial growth of Macrophomina phaseolina to varying degrees. Complete inhibition (100%) of growth of pathogen over control was observed in Carboxin 37.5% + Thiram 37.5% WP followed by Mancozeb 63% WP + Carbendazim 12% WP with mycelial growth inhibition percentage of 98.79%. Among the commercially available botanicals, fungal and bacterial biocontrol agents Neem oil, Trichoderma viride (Tv1) and Pseudomonas fluorescens (Pf1) were effectivewithmycelial growth inhibition percentage of 27.05, 71.05, 40.58 per cent, respectively.